Решить этот пример sin2x+sinx=2cosx+1

Решить этот пример sin2x+sinx=2cosx+1

  • Sin(2x)+sin(x)=2cos(x)+1

    2sin(x)cos(x)+sin(x)=2cos(x)+1

    sin(x)*(2cos(x)+1)=2cos(x)+1

    sin(x)*2cos(x)+1)-1*(2cos(x)+1)=0

    (sin(x)-1)(2cos(x)+1)=0

    1) sin(x)-1=0

    sin(x)=1

    x=pi/2 +2pi*n

    2) 2cos(x)+1=0

    2cos(x)=-1

    cos(x)=-1/2

    x=arccos(-1/2)+2*pi*n

  • sin2x+sinx=2cosx+1

    sinx(2cosx+1) - (2cosx+1) = 0

    (2cosx+1)(sinx-1) = 0

    Разбиваем на 2 уравнения:

    2cosx+1 = 0 sinx-1 = 0

    cosx=-1/2 sinx = 1

    ^+_{-}frac{2pi}{3} + 2pi*k;          frac{pi}{2} + 2pi*n;   k,n:  Z.


Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *